Protein Association in Living Cells Using Fret Spectrometry: Application to G-Protein Coupled Receptors - (:unkn) unknown (My University, 2013)
Recent advancements in fluorescence microscopy coupled with newly developed fluorescent tags have transformed Fluorescence (Förster) Resonance Energy Transfer (FRET) into a powerful tool studying in vivo molecular interactions with improved spatial (angstrom) resolution. Though widely used to study protein-protein interactions, generalizing and testing the FRET theory for oligomeric complexes containing multiple donors and acceptors has only become possible in recent years. Therefore, many aspects of it are yet unexplored. In this work, we tested the kinetic theory of FRET using linked fluorescent proteins located in the cytoplasm or at the plasma membrane. We used a novel method developed in our lab that combines an optical micro-spectroscope (OptiMiS) with a simple kinetic theory of FRET that relates the number and relative disposition of monomers within an oligomer to the measured FRET efficiency in terms of the pair-wise FRET efficiencies for an individual donor-acceptor pair in the oligomer. Using this framework, we showed that the measured FRET efficiencies of obligate trimers and tetramers in living cells are correctly predicted by the kinetic theory of FRET. The method was then used to study the oligomerization of G-protein coupled receptors (GPCRs), which are cell surface signaling proteins that constitute a large family of drug targets. The literature on GPCR homo-oligomerization encompasses conflicting views that range from interpretations that GPCRs must be monomeric, through comparatively newer proposals that they exist as dimers or higher-order oligomers, to suggestions that such quaternary structures are rather ephemeral or merely accidental and may serve no functional purpose. We used a novel FRET framework together with Optical Micro Spectroscopy (OptiMiS) technology and controlled expression of energy donor-tagged species of muscarinic M3 acetylcholine receptor, a GPCR of interest, to show that M3R exists as stable dimeric complexes at the plasma membrane, a large fraction of which interacts dynamically to form tetramers without the presence of trimers, pentamers, hexamers, etc. This was also supported by co-immunoprecipitation of receptors synthesized at distinct times. Based on these findings, we proposed a conceptual model that may reconcile the conflicting literature views on the quaternary structure of GPCRs.